A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters - Kolicka, Małgorzata; Gadawski, Piotr; Dabert, Miroslawa (European Journal of Taxonomy, 2017)
Gastrotricha is a cosmopolitan phylum of aquatic and semi-aquatic invertebrates that comprises about 820 described species. Current knowledge regarding freshwater gastrotrichs inhabiting caves is extremely poor and there are no extant data regarding Gastrotricha from Montenegro. We describe a new species from Obodska Cave, which is also the first record of a gastrotrich from this region. Due to its unusual habitat and morphological characteristics, this species may be important when considering the evolution and dispersion routes of Chaetonotidae Gosse, 1864 (sensu Leasi & Todaro 2008). We provide morphometric, molecular and phylogenetic data for the new species, together with photomicrographs and drawings.